PEMANFAATAN E-SCRAPBOOK DALAM PEMBELAJARAN DI PGSD - Yosef Yosef; Iramawati Iramawati; Rusnawati Rusnawati (Universitas Sriwijaya, 2014)
Abstract: The using of e-scrapbook in teaching at primary teacher education is intended to improve teaching and learning quality applying inductive approach. Participants of this classroom action research are required to create e-scrapbook and to have deep understanding proved through presentation in class and learning achievement. The results of the study shows that teaching quality is improved as indicated by quality of students’ e-scrapbook, their ability to communicate the e-scrapbooks to their peers, and their more satisfying-learning achievement. It is recommended to instructors of primary teacher education to use e-scrapbook as a means of delivering instructional materials as well as to involve their students in creating it. Abstrak: Pemanfaatan e-scrapbook(elektronik scrapbook) dalam pembelajaran di PGSD ditujukan untuk meningkatkan kualitas pembelajaran berpendekatan induktif. Mahasiswa yang berpatisipasi dalam penelitian dipersyaratkan untuk mengemas e-scrapbook dan memiliki pemahaman mendalam dibuktikan melalui paparan dan hasil belajar. Hasil-hasil penelitian tindakan ini menunjukkan adanya peningkatan mutu pembelajaran seperti diindikasikan oleh kualitas e-scrapbook yang dikemas mahasiswa, kemampuan dalam mengkomunikasikan isi e-scrapbook kepada sebaya di kelas, capaian hasil belajar yang lebih memuaskan. Pemanfaatan e-scrapbook direkomendasikan bagi dosen pengampu mata kuliah yang memanfaatkan bahan ajar alternatif berikut keterlibatan aktif mahasiswa dalam pengemasannya. Kata Kunci: e-scrapbook, PGSD, penelitian tindakan